Evaluation of the Glucose-Lowering Effect of Bloodletting Therapy in Type 2 Diabetes Mellitus - Tserentogtokh Baasantogtokh; Sainbileg Sonomtseren; Tsolmon Unurjargal; Rinchyenkhand Myagmardorj; Vaanchigsuren Seesregdorj; Bayarmagnai Lkhagvasuren; Vankhuu Enkhtuya; Seesregdorj Surenjid (Central Asian Journal of Medical Sciences)
Objective: This study uses a quantitative method to evaluate bloodletting therapy’s impact on lowering blood glucose levels and improving metabolic parameters in patients with type 2 diabetes mellitus (T2DM). Method: This randomized, controlled clinical trial included 110 patients diagnosed with T2DM who met the study’s inclusion criteria. Participants were randomly assigned to a control group (standard medication) and an experimental group (standard medication plus bloodletting therapy). Both groups received medicine according to the Mongolian Clinical Practice Guidelines for T2DM treatment. The experimental group additionally underwent bloodletting therapy on Day 6 of the study, following a 5-day preparation period during which they consumed 2.0 grams of a “3-seed decoction” (twice daily). The bloodletting procedure involves drawing blood from the posterior antebrachial vein (100-150 mL). The study evaluated primary outcomes, including fasting blood glucose and HbA1c levels, and secondary outcomes, such as insulin levels, C-peptide concentrations, and lipid profiles (total cholesterol, triglycerides, LDL, and HDL) at baseline, Day 30, and Day 60. Results: The experimental group demonstrated significant improvements in metabolic parameters. BMI levels decreased from 30.45±4.48 at baseline to 29.09±3.60 at Day 60 (P < 0.05), and HbA1c decreased from 9.2 ± 2.46% to 8.49 ± 1.85% (P< 0.05). Furthermore, significant reductions were observed in insulin levels (from 43.38 ± 14.12 to 25.61 ± 4.8 pmol/L; P= 0.0001) and C-peptide levels (from 4.9 to 4.2 ng/mL; P= 0.0004). The lipid profile also showed improvements, with a reduction in LDL cholesterol and triglycerides compared to the control group, although these changes were not statistically significant at Day 60. Conclusion: Integrating bloodletting therapy into the treatment regimen for T2DM provides additional benefits, including significant reductions in blood glucose, HbA1c, insulin, and C-peptide levels. Bloodletting therapy, when used in combination with standard pharmacotherapy, could offer a cost-effective and clinically beneficial treatment option for managing type 2 diabetes.